The Nigerian language policy: theory or practice? (2013)
The language provision in the National Policy of Education (l977) prescribes among others that 'in the interest of national unity, each child should be encouraged to learn one of the three major languages' (i.e. Hausa, Igbo, and Yoruba), Scholars have frowned at the language used in couching the recommendations. For instance, Bamgbose (2000b) opines that some 'escape-clauses' were woven into the recommendations, such that stakeholders in education can violate them with impunity. This study was carried out to find out whether the three major languages are being taught in secondary schools as subtly prescribed by the language policy. In the course of the study, thirty-five schools spread across three states - Oyo, Ogun, and Lagos - were sampled. Information gathered show that Yoruba is taught in all the schools, whereas Hausa, Igbo and Yoruba are taught only in four of them, while Igbo is taught in seven of them. From this, we deduced that only four schools teach the three major languages. Three of them are located in Lagos State while one is located in Oyo State. None of the schools visited in Ogun State teaches the three major languages